2016
DOI: 10.1002/2015ja021540
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of plasmaspheric plumes and ionospheric outflows observed at the dayside magnetopause

Abstract: We present a statistical study of plasmaspheric plumes and ionospheric outflows observed by the Cluster spacecraft near the dayside magnetopause. Plasmaspheric plumes are identified when the low‐energy ions (<1 keV) with ∼90° pitch angle distributions are observed by the Cluster Ion Spectrometer/Hot Ion Analyzer instrument. The ionospheric outflows are characterized by unidirectional or bidirectional field‐aligned pitch angle distributions of low‐energy ions observed in the dayside magnetosphere. Forty‐three (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 80 publications
3
65
1
1
Order By: Relevance
“…Cold ions (up to few tens of eV) often reach the dayside magnetopause [e.g., Sauvaud et al, 2001;André and Cully, 2012;Lee et al, 2016;Chandler and Moore, 2003;Chen and Moore, 2006] and participate in reconnection [e.g., Chandler et al, 1999;Chen and Moore, 2004]. They belong to the plasma cloak, plasmaspheric wind, or plasmaspheric drainage plumes [e.g., Chappell et al, 2008;Darrouzet et al, 2008].…”
Section: Citationmentioning
confidence: 99%
“…Cold ions (up to few tens of eV) often reach the dayside magnetopause [e.g., Sauvaud et al, 2001;André and Cully, 2012;Lee et al, 2016;Chandler and Moore, 2003;Chen and Moore, 2006] and participate in reconnection [e.g., Chandler et al, 1999;Chen and Moore, 2004]. They belong to the plasma cloak, plasmaspheric wind, or plasmaspheric drainage plumes [e.g., Chappell et al, 2008;Darrouzet et al, 2008].…”
Section: Citationmentioning
confidence: 99%
“…Sometimes, a plume of dense plasma will extend from the main body of the plasmasphere (e.g., Sandel et al, 2003) and can be observed near the dayside magnetopause (e.g., Lee et al, 2016). The plume ions are characterized by being perpendicular to magnetic fields, in contrast to the generally field-aligned ionospheric outflow ions (e.g., Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The plasmapause locations are marked by the vertical red curves, on basis of the method of Moldwin et al (2002), with the outbound one at L~3.7 and the inbound one at L~4.0. These two plume crossings were on the postmidnight to dawnside, which is rare according to the statistics of plasmaspheric plume (e.g., Darrouzet et al, 2008;Lee et al, 2016;Moldwin et al, 2004). As shown as shaded regions, one occurred at 1610-1800 UT Zoom-in plots of these two time intervals are shown in Figures 1b and 1c to provide detailed information of the ambient electron density and the spatial location defined by L-shell, MLT, and magnetic latitude (MLAT) for the plume.…”
Section: Observations Of a Nightside Plume And Hiss Emissionsmentioning
confidence: 99%
“…• Moderately strong hiss emissions can occur to peak at~100 Hz within the two crossings of a pronounced post-midnight-to-dawn plume • Plasmaspheric hiss in the nightside plume is efficient to pitch angle scatter~10-100 keV electrons • With the resultant electron loss timescales varying over 3 orders of magnitude, hiss emissions in the nightside plume can account for the fast loss of ≲100 keV electrons and for the slow decay of higher energy electrons occurrence rate increasing with the solar wind dynamic pressure (e.g., Darrouzet et al, 2008;Lee et al, 2016;Moldwin et al, 2004). In addition to hiss-induced electron scattering in the plasmasphere, hiss in plumes can also resonate with radiation belt electrons.…”
Section: 1029/2018gl077212mentioning
confidence: 99%
See 1 more Smart Citation